Land application of municipal sewage sludge: Human health risk assessment of heavy metals - Yakamercan, Elif; Ari, Akif; Aygün, Ahmet (Elsevier Ltd, 2021)
Land application of municipal sewage sludge has become an attractive option and disposal method used worldwide. Hence, the suitability of the sludge with regards to toxic and carcinogenic chemicals is crucial to prompt informed decisions regarding its use on agricultural areas. This study aims to assess ecological and human health risks of heavy metals in sewage sludge samples collected from 22 different cities' wastewater treatment plants to determine their agricultural application potential in Turkey. The average metal concentrations of the samples decreased as the following order of Zn > Cu > Cr > Pb > Ni > Mo > As > Cd > Se > Hg without a significant seasonality. To evaluate the carcinogenic and non-carcinogenic health risks, site-specific overall total cancer risk (TCR) and Hazard Index (HI) values were calculated as the sum of all heavy metals’ ingestion, inhalation, and dermal contact exposures for children and adults. Contribution of the inhalation exposure due to the dust re-suspension during agricultural work to the total health risk has seemed be negligible when compared to ingestion and dermal contact. The carcinogenic risk for the adults were within the acceptable range (10−6 to 10−4) proposed by USEPA based on our estimations (2.4 ✕ 10−5), but the risk value was slightly exceeded the safe levels for children (1.6 ✕ 10−4). Similarly, HI values for adult subjects were below the reference value of 1, whereas they were higher for children (up to 2.52). Pb, As, and Cr were the major contributing metals to carcinogenic risks for both children and adults. Although the heavy metal concentration of collected samples was within the agricultural land application legal standards proposed by the Environmental Protection Agency (EPA) and the Ministry of Environment and Urbanization of Turkey (MEU), but the results of human health risk assessments showed that the risks may occur especially for sensitive individuals like children. This study showed that the evaluation of waste materials such as municipal sewage sludge should be applied only if it is proper for both ecological and health-safe, and assessing based on the regulatory limit values would not be enough to protect all population.
Keywords: Agricultural application; Health hazard assessment; Heavy metal; Sewage sludge